A Trusted Social Network Using Hypothetical Mathematical Model and Decision- Based Scheme; IEEE Access; Vol. 9 - Rathee G. Geetanjali; Garg S. Sahil; Kaddoum G. Georges; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Piran J. Jalil; Muhammad G. Ghulam (2021, 2021)
Title screen